Study of Seulawah Agam’s Geothermal Source Using Gravity Method - Marwan Marwan; Ibnu Rusydy; Gartika Setiya Nugraha; Asrillah Asrillah (Jurnal Natural, 2014)
Gravity method was carried out at Seulawah Agam Area to delineate the existence of geothermal source, which is specifically existed in both the geothermal filed of Heutsz’s Crater and.Cempaga’s Crater. The Seulawah Agam is located in Aceh Besar district. Geologically, the area is dominated by volcanic mudflow and Lam Teuba’s rocks having age from Tersier to Resen Period. The equipment used includes Gravimeter CG-5 Autograv, Portable GPS (Global Positioning System), Navigation type (map of the survey area), computer and the other technical supports, such as handy talky, umbrella, watch, pens and observed data notes. This research was conducted by doing two stages.  Firstly, establishing the base station which is a reference point for all gravity data measurements at each point. Secondly, measuring gravity data at each point by repeating three times following looping pattern as pathway of measurement either in Heutsz’s crater whose nine points recording or in Cempaga’s crater whose seventeen points. The data was simply processed using Microsoft Excel that can just plot the Bouguer anomaly and interpreted qualitatively due to preliminary research. The resultof this research has shown that both areas have two kinds of Bougeur anomalies which slightly attract attention who’s high and low anomaly. At Heutsz’s Crater has high and low density existed at F125 FR and B6 point. The Point whose high density means that it was formed mineralization by hydrothermal process through fracture materials, meanwhile the point whose low density indicates that there is existed the fault which is quite related to Seulimum’s Fault based on Aceh map. This result is also same as obtained at Cempaga’s Crater which means also same interpretation. In addition, it can be sum up that fault zones are essentially important in geothermal system that plays vital role in term of fluid circulation. Employing the gravity method in this research effectively can be said